2017
DOI: 10.1016/j.nrl.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Consenso para el tratamiento de la esclerosis múltiple 2016. Sociedad Española de Neurología

Abstract: With the advent of new disease-modifying drugs, the treatment of multiple sclerosis is becoming increasingly complex. Using consensus statements is therefore advisable. The present consensus statement, which was drawn up by the Spanish Society of Neurology's study group for demyelinating diseases, updates previous consensus statements on the disease. The present study lists the medications currently approved for multiple sclerosis and their official indications, and analyses such treatment-related aspects as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 39 publications
0
5
0
7
Order By: Relevance
“…Recent meta-analysis confirmed that alemtuzumab, natalizumab, and fingolimod are the best available choices for preventing clinical relapses in patients with RRMS ( 30 ). However, there is no consensus algorithm available despite the publication of national or regional recommendations ( 8 , 16 , 26 , 31 33 ). As a result, the current landscape of DMTs for the treatment of RRMS includes first-line therapies (beta interferons, glatiramer acetate, teriflunomide, and dimethyl fumarate) and second-line therapies (fingolimod, natalizumab, and alemtuzumab).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analysis confirmed that alemtuzumab, natalizumab, and fingolimod are the best available choices for preventing clinical relapses in patients with RRMS ( 30 ). However, there is no consensus algorithm available despite the publication of national or regional recommendations ( 8 , 16 , 26 , 31 33 ). As a result, the current landscape of DMTs for the treatment of RRMS includes first-line therapies (beta interferons, glatiramer acetate, teriflunomide, and dimethyl fumarate) and second-line therapies (fingolimod, natalizumab, and alemtuzumab).…”
Section: Methodsmentioning
confidence: 99%
“…Therapeutic inertia (TI) is a term introduced in 2006 to define the absence of treatment initiation or intensification in patients when treatment goals are unmet ( 11 14 ). In the context of MS, TI is defined as the lack of treatment initiation or escalation when there is evidence of disease activity (based on the clinical course and neuroimaging markers) ( 15 , 16 ). It is possible that aversion to ambiguity contributes to TI as the probabilities of benefits with treatment escalation are typically less well known than with treatment continuation.…”
Section: Introductionmentioning
confidence: 99%
“…Se caracteriza por presentar brotes intercalados con etapas de remisión, aunque su incidencia disminuye durante la enfermedad [1] . En pacientes con una buena respuesta al tratamiento, la tasa anualizada de brotes es de 0,5 [30] . Debido a que los pacientes a menudo no llegan a recuperarse completamente, estos episodios suelen generar un aumento acumulado de la discapacidad [1,31,32] .…”
Section: Fenotipos Principalesunclassified
“…c Se refiere al tratamiento modificador del curso de la enfermedad, diferente del tratamiento sintomático [1,3,7,30] .…”
Section: Carga Económica De La Emunclassified
“…The tendency to stay with the status quo is called “therapeutic inertia” and defined as the absence of treatment initiation or intensification when treatment goals are unmet ( 15 18 ). In the context of MS, TI is defined as the lack of treatment initiation or escalation when there is evidence of disease activity (based on the clinical course and neuroimaging markers) ( 19 , 20 ). Treatment escalation has been shown to reduce relapse rates, disability progression, and MRI activity ( 21 24 ).…”
Section: Introductionmentioning
confidence: 99%